2000
DOI: 10.1111/j.1530-0277.2000.tb04642.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Ethanol and the First Suckling Episode in the Newborn Rat

Abstract: These findings suggest a dissociation between acute ethanol effects on suckling and overall motor activity, with suckling apparently less sensitive to suppressive and more sensitive to activating effects of ethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
1
8
1
Order By: Relevance
“…In summary, the present data together with results of our previous studies [11], [15], [19] suggest a substantial role of pharmacological effects of ethanol (positive, stimulatory and sedative, inhibitory) in age-related differences of ethanol acceptance and indicates that sensitivity of ingestive behavior to the pharmacological effects of ethanol changes between postnatal days 9 and 12.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In summary, the present data together with results of our previous studies [11], [15], [19] suggest a substantial role of pharmacological effects of ethanol (positive, stimulatory and sedative, inhibitory) in age-related differences of ethanol acceptance and indicates that sensitivity of ingestive behavior to the pharmacological effects of ethanol changes between postnatal days 9 and 12.…”
Section: Discussionsupporting
confidence: 83%
“…Palatability of various tastants, including ethanol, has been measured in adults by analysis of short latency motor and affective reactions to intraoral infusions of small amounts of flavored fluid [9], [10]. However, assessment of taste responsiveness in the neonatal rat has usually been based on intake measured in relatively long procedures (10-20 minutes) when the animal consumed a substantial amount of ethanol (2.5% of body weight) [1], [11], [12], [13], [14], [15], [16]. With such tests it is difficult to distinguish between changes in orosensory properties of ethanol and postingestive consequences of ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…The lower weight gain in our PAE rats may be indirectly related to a decrease in maternal grooming behavior. Although studies with neonatal rats have shown that exposure to high doses of EtOH can impair sucking behavior, leading to a decrease in body weight gain (Cheslock et al, 2000), we did not detect significant alterations in nursing time, suggesting that alternative mechanisms are responsible for the growth deficits observed in our rats. Studies suggest that EtOH may stunt postnatal growth by interfering with the actions of insulin and insulin-like growth factor (Aros et al, 2011; Ting and Lautt, 2006).…”
Section: Discussioncontrasting
confidence: 81%
“…The development of experimental procedures for control of the acquisition, expression, or both of memories defined by alcohol's aversive components could aid in the analysis of possible positive-and negative-reinforcement capabilities of alcohol. This strategy should also provide a tool that can easily be used across different ontogenetic stages of development-an opportunity that is particularly important when considering recent studies that suggest substantial appetitive reinforcing properties of alcohol during very early postnatal life (Cheslock et al 2000(Cheslock et al , 2001Petrov et al, 1999).…”
Section: Figmentioning
confidence: 99%